Neuromicrobiology, an emerging neurometabolic facet of the gut microbiome? - Miri, Saba; Yeo, JuDong; Abubaker, Sarah; Hammami, Riadh (Frontiers in Microbiology, 2023)
The concept of the gut microbiome is emerging as a metabolic interactome influenced by diet, xenobiotics, and other environmental factors that affect the host’s absorption of nutrients, metabolism, and immune system. Beyond nutrient digestion and production, the gut microbiome also functions as personalized polypharmacy, where bioactive metabolites that our microbes excrete or conjugate may reach systemic circulation and impact all organs, including the brain. Appreciable evidence shows that gut microbiota produce diverse neuroactive metabolites, particularly neurotransmitters (and their precursors), stimulating the local nervous system (i.e., enteric and vagus nerves) and affecting brain function and cognition. Microbiome-targeted interventions are seen as promising adjunctive treatments, but the mechanisms underlying host-microbiome interactions have yet to be established, thus preventing informed, evidence-based therapeutic applications. In this paper, we review the current state of knowledge for each of the major classes of microbial neuroactive metabolites, emphasizing their biological effects on the microbiome, gut environment, and brain. Also, we discuss the biosynthesis, absorption, and transport of gut microbiota-derived neuroactive metabolites to the brain and their implication in mental disorders.